Liver Transplant in Hepatocellular Carcinoma: Indication and Prognostic Factors - Gunawan - -; Irsan Hasan; Juferdy Kurniawan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Hepatocellular carcinoma (HCC) is the most common type of liver cancer. There are several treatment modalities according to Barcelona treatment algorithm. Liver transplant is one of the curative option treatments, with its indication and prognostic factors. Carefully selected patients for liver transplant in HCC case will result in the same or slightly inferior survival rate compare with liver transplant in non-malignancy case.